Medical Rehabilitation Program for Knee Osteoarthritis: A Narrative Review - Rahmaddiansyah, Refa; Yolanda, Riri Prima; Agustin, Rini (Faculty of Medicine, Universitas Andalas, 2024)
Background: Osteoarthritis is the most prevalent degenerative joint disease, increases with age in Indonesia, affects all ethnicities, more in women, and is a leading cause of long term disability in adults 65 years or older. Prolonged NSAID use may cause gastritis, bleeding, and renal injury. Objective: To synthesize current understanding of osteoarthritis burden, mechanisms, and patient centered management. Methods: Narrative review of recent evidence on epidemiology, pathophysiology, clinical features, and treatment guidance. Results: Symptoms develop gradually and may accelerate after injury or overload. Drivers include joint aging, trauma or overuse, genetics, obesity, and hormonal factors. First line care comprises education, weight control, physical therapy, and structured exercise. Analgesics and NSAIDs with risk mitigation, intra articular injections, and assistive devices are added by severity and joint involvement. Early multimodal strategies reduce pain, improve function and quality of life, and may slow progression. Outcomes worsen with muscle weakness, obesity, and depression. Conclusion: Osteoarthritis is common yet manageable. Stratified individualized care started early and balanced for benefit and risk preserves mobility and independence and reduces complications.